Role of digital learning pedagogy in remediating learning disability - Kaur, Paramjeet; Cheema, Guneetkaur (Journal of Interdisciplinary Studies in Education, 2024)
Recent studies have indicated that digital platforms cannot amalgamate learning solutions for students with learning disabilities. In this paper, we provide a comprehensive overview of the literature on the topic and methods to elaborate on earlier studies on learning disabilities. These findings can help new researchers develop effective techniques to improve learning skills, and cognitive development and motivate teachers toward remediation programs to overcome the problem of learning disability.